Good Vibrations : Brian Wilson and the Beach Boys in Critical Perspective - Lambert, Philip (2016)
Good Vibrations brings together scholars with a variety of expertise, from music to cultural studies to literature, to assess the full extent of the contributions to popular culture and popular music of one the most successful and influential pop bands of the twentieth century. The book covers the full fifty-year history of the Beach Boys' music, from essays on some of the group's best-known music-such as their hit single "Good Vibrations" -to their mythical unfinished masterpiece, Smile. Throughout, the book places special focus on the individual whose creative vision brought the whole enterprise to life, Brian Wilson, advancing our understanding of his gifts as a songwriter, arranger, and producer